Schizophrenia and Hereditary Polyneuropathy: PMP22 Deletion as a Common Pathophysiological Link? - Endres, Dominique; Maier, Simon J.; Ziegler, Christiane; Nickel, Kathrin; Riering, Anne N.; Berger, Benjamin; Lambeck, Johann; Fritz, Miriam; Gläser, Birgitta; Stock, Friedrich; Dacko, Michael; Lange, Thomas; et al. (Frontiers in Psychiatry, 2019)
Background. Schizophrenic disorders are common and debilitating due to their symptoms, which can include delusions, hallucinations, and other negative symptoms. Organic forms can result from various cerebral disorders. In this paper, we discuss a potential association between schizophrenia and hereditary polyneuropathies (PNPs). Case presentation. We present the case of a 55-year-old female patient with chronically paranoid–hallucinatory schizophrenia, severe cognitive deficits since the age of 30, and comorbid repeated focal pressure neuropathies beginning at age 20. At the age of 35, genetic testing revealed a deletion on chromosome 17p12 covering the peripheral myelin protein 22 gene (PMP22), which led to the diagnosis of hereditary neuropathy with liability to pressure palsy (HNPP). Cerebral magnetic resonance imaging showed internal atrophy, magnetic resonance spectroscopy found alteration of the glutamate and myo-inositol levels in the anterior cingulate cortex, neuropsychological testing showed deficits in working memory and psychomotor speed, and electrophysiological testing detected signs of sensorimotor demyelinating PNPs (accentuated in the legs). Conclusion. There may be an association between schizophrenia and HNPP. In observational studies, the deletion of interest (chromosome 17p12) was nearly 10 times more common in schizophreniform patients than in controls. This potential association could be pathophysiologically explained by the role of PMP22, which is mainly expressed in the peripheral nervous system. However, PMP22 mRNA and protein can also be found in the brain. PMP22 seems to play an important role in regulating cell growth and myelination, functions that are disturbed in schizophrenia. Such a connection obviously cannot be clarified on the basis of one case. Future studies should analyze whether patients with HNPP exhibit increased rates of psychotic disorders, and patients with schizophrenia and repeated focal pressure neuropathies should be examined for the PMP22 mutation. Alternatively, the co-occurrence of schizophrenia and HNPP could be coincidental.